A blueprint for a safer planet : how to manage climate change and create a new era of progress and prosperity - Stern, Nicholas (London, 2009)
"Further substantial climate change is unavoidable and the risks to the natural world, the economy and our everyday lives are immense. The way we live in the next thirty years – how we invest, use energy, organise transport and treat forests – will determine whether these risks become realities. Although poor countries – the least responsible for climate change – will be hit earliest and hardest, all countries must adapt to the effects: hurricanes and storms strike New Orleans and Mumbai; flooding causes devastation in England and Mozambique; droughts occur in Australia and Darfur; and sea level rise will affect Florida and Bangladesh. Lord Stern, author of the Stern Review on the Economics of Climate Change and former Chief Economist at the World Bank, is the world’s leading authority on what we can do in the face of such unprecedented threat. Action on climate change will require the greatest possible international collaboration, but if successful will ensure not just our future, but our future prosperity. Focusing on the economic management of investment and growth from the perspective of both adaptation and mitigation, Stern confronts the most urgent questions facing us now: what is the problem? What are the dangers? What can be done to reduce emissions, at what cost? How can the world adapt? And what does all this mean for corporations, governments and individuals?"